Cyclic di‐GMP inactivates T6SS and T4SS activity in Agrobacterium tumefaciens. Issue 2 (4th June 2019) - McCarthy, Ronan R.; Yu, Manda; Eilers, Kira; Wang, Yi‐Chieh; Lai, Erh‐Min; Filloux, Alain
Summary: The Type VI secretion system (T6SS) is a bacterial nanomachine that delivers effector proteins into prokaryotic and eukaryotic preys. This secretion system has emerged as a key player in regulating the microbial diversity in a population. In the plant pathogen Agrobacterium tumefaciens, the signalling cascades regulating the activity of this secretion system are poorly understood. Here, we outline how the universal eubacterial second messenger cyclic di‐GMP impacts the production of T6SS toxins and T6SS structural components. We demonstrate that this has a significant impact on the ability of the phytopathogen to compete with other bacterial species in vitro and in planta . Our results suggest that, as opposed to other bacteria, c‐di‐GMP turns down the T6SS in A. tumefaciens thus impacting its ability to compete with other bacterial species within the rhizosphere. We also demonstrate that elevated levels of c‐di‐GMP within the cell decrease the activity of the Type IV secretion system (T4SS) and subsequently the capacity of A. tumefaciens to transform plant cells. We propose that such peculiar control reflects on c‐di‐GMP being a key second messenger that silences energy‐costing systems during early colonization phase and biofilm formation, while low c‐di‐GMP levels unleash T6SS and T4SS to advance plant colonization. Abstract : Agrobacterium tumefaciens is a plant pathogen capable of causing tumorigenesis in a wide variety of plant species. In this study, we show how the bacterial second messenger, cyclic‐di‐GMP, is a key regulator of both plant pathogenesis and interbacterial competition in A. tumefaciens .